Study of Novels of Bapsi Sidhwa - Sharma, Dr. Dinesh (Innovative Research Thoughts, 2017)
Bapsi Sidhwa, in her works, explores the nature of women's oppression in postcolonial South Asia, a region with a long history of gender-based violence and sexual stereotypes and roles. Through her works, Bapsi Sidhwa aims to change the way society views women. In her works, Sidhwa takes a sexist stance towards South Asian culture. To study and analyse the mechanisms of old patriarchal civilizations, and the colonial or patriotic efforts to control women in post-colonial South Asia, she devotes much of her novels to this task